Peranan Bimbingan Konseling Bagi Guru Sekolah Dasar Se- Kecamatan Kuantan Hilir Seberang Kabupaten Kuantan Singingi - Khadijah, Khairiyah; Mardes, Siska (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2022)
This service activity aims to enable participants to organize a Counseling Guidance programfor students. This Counseling Guidance can help solve or prevent problems for students atschool and in the family. The methods for implementing community service activities arelectures, demonstrations, and simple exercises in implementing guidance programs forstudents in elementary schools. The target of training activities in implementing thiscounseling guidance program is elementary school education teachers in Kuantan HilirSeberang District, Kuantan Singingi Regency. Outcomes of Service Activities: (a) elementaryschool education teachers understand the basic concepts of counseling guidance, (b) basicconcepts of counseling guidance in elementary schools, (c) Simple practice of implementingcounseling guidance programs (types of BK services) tailored to student needs (c) primaryschool education teachers can implement types of counseling and guidance services that canbe applied in primary school education, (f) discussions and questions and answers to discussand explain things that participants as feedback for the trainer do not understand. Then, afterthe activity implementation, a new understanding was obtained for elementary schoolteachers that they could use BK services to solve student problems according to student needs,whereas homeroom teachers at the elementary school level.